El takanakuy chumbivilcano: las aporías de la racionalización de la cultura en que incurren el Estado y los medios de comunicación - Hernández Lefranc, Harold (2023)
The takanakuy is a periodic and cyclical festival complex that takes place mainly in some towns in the pro-vince of Chumbivilcas, department of Cusco, and that is expressed visibly and prominently in a sum of fist and kick fights between pairs of men, representatives family groups or villages, including adolescents and children, and that in the last twenty years has spread to women. Despite the manifest diffusion of the exis-tence of this festivity of the takanakuy throughout Peru, in the last at least fifteen years, thanks to the access of the media and the internet, and to the fact that the State in 2016 declared the huaylía of Chumbivilcas , which accompanies the takanakuy, «Cultural Heritage of the Nation», this report postulates —as it will be sustained and demonstrated based on extensive fieldwork and reading of relevant sources— that this supposed closeness, affinity or empathy, of institutions outside of Chumbivilcas with this playful, ritualized and proto-sports violence, it’s not so real This is fundamentally corroborated in the critical, distant, uncomfortable, reprehensible and censoring reading that the different institutionalizations unrelated to this practice make of the curbed form of violence that occurs in the takanakuy; and in doing so they do nothing more than reveal the aporias of the rationalization of the culture in which they incur.